Cement nanocomposites containing montmorillonite nanosheets modified with surfactants of various chain lengths - Oh J.-A.; Zhuge Y.; Araby S.; Wang R.; Yu H.; Fan W.; Liu M.; Lee S.-H.; Alam M.J.; Ma J. (Elsevier Ltd, 2023)
Cements; Chain length; Clay minerals; Compressive strength; Dispersions; Durability; Morphology; Nanocomposites; Nanosheets; Alkyl chain lengths; Composite morphology; Hydration degree; Mechanical performance; Montmorillonite (MMT); Organic surfactants; Surfactant chain length; Water penetration; Surface active agents